One duke down - Bennett, Anna (Romance novelist) (Bennett, Anna (Romance novelist). Rogues to lovers novel, 2023)
"Miss Poppy Summers is determined to keep her family's fishing business afloat. Her poor widowed father has fallen ill, and her foolhardy brother has moved to London, leaving her precious little time to read or pursue her own dreams. But she'll do anything for her family, so she cheerfully spends mornings in her rowboat, casting her nets. The very last thing Poppy expects or wants to find tangled in them is a dangerously attractive man. Especially one with a head wound--who's convinced he's a duke. Andrew Keane is the Duke of Hawking, but he's having the devil of a time convincing his fiery-haired rescuer of that fact. The truth is he came to the seaside resort of Bellehaven Bay to escape his life in London. Unfortunately, someone in Bellehaven wants to kill him--and he intends to find out who. He implores Poppy to tend to his injuries and hide him on her beach, reasoning it will be easier to find his attacker if that man assumes Keane is already dead. She wants no part of the scheme but can't refuse the generous sum he offers in exchange for food and shelter while he recovers. It's a mutually beneficial business arrangement ... nothing more"--